SugarBun Limbang, Sarawak / Zulkifli Abdul Hadi, Khairun Nisaa Khairuddin ... [et al.] - Abdul Hadi, Zulkifli; Khairuddin, Khairun Nisaa; Richard, Richroy; Gunap, Timothy (2019)
The main objective of this assignment is identifying the problems, choosing the solutions and implementing the activities that will enhance the long-term performance and productivity of SugarBun Limbang. This can be done by setting up direction and creating compatibility between the internal skills and resources of the organisation and the changing external environment within which it operates. SWOT analysis was used to justified and understanding SugarBun Limbang's Strengths and Weaknesses and for identifying both the Opportunities for the restaurants future. Besides that, SWOT Analysis helps SugarBun Limbang to carve a sustainable achivement and performance in their market.